A techno-economic assessment of power-to-gas to produce hydrogen by TALOS - Matthew Hawkins; Daniel Mills; Muzaffar Bandarkar; Peter Ackroyd; Farouq Saifudin; George Aggidis; Giuseppe Bagnato (Fuel Processing Technology)
The transition toward a low-carbon energy system encourages academicians to research innovative energy solutions. Diversifying renewable energy sources ensures the effort to fulfil market demand comes into being. This study presents a comprehensive techno-economic assessment of Power-to-Gas technology to produce hydrogen using TALOS-WEC as energy converter from wave energy to electricity. Power-to-Gas is a technology that converts electrical energy into gaseous fuel and TALOS-WEC is a novel multiple degree of freedom wave energy converter developed by Lancaster University, UK. The system in the study utilises a decommissioned offshore oil platform and uses seawater as a raw material, which brings forward the advantage of abundance. The study considers separation, electrolysis, compression or liquefaction, and a transportation system. An economic analysis and economic potential study has been done for each system and then a levelized cost of energy analysis has been calculated. A process flow diagram of the plant can be seen for the purpose of visualising the system setup. The LCOE of the suggested technology is at 123.19 $/MWh and the cost breakdown shows that the decommissioned oil platform will cost the most at 32.5 M $/yr followed by hydrogen compression technology and TALOS at 1.6 M$/yr and 1.5 M$/yr respectively for the stated operating period. This study has shown optimistic results for the Power-to-gas technology, but further research and development needed for TALOS-WEC to become feasible for the system.